The Analysis of Students’ Grammar Mastery in Tenses at SMK Sinar Husni Medan - Khairuna Humairah; Nurul Hasanah; Yoel Hernandes Silalahi; Juliana Juliana (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to analyse the level of students' grammar mastery in tenses at SMK Sinar Husni Medan. The study focuses on evaluating students' proficiency in understanding and applying grammatical tenses, a crucial aspect of language learning. The research employs a mixed-methods approach, combining quantitative data through assessments and qualitative insights gathered from interviews and observations. The sample comprises twelfth grade students in SMK Sinar Husni Medan. Data was collected from tests, classroom observations, and interviews with both students and teachers. Qualitative data are gathered through classroom observations and interviews with students and teachers. Observations focus on instructional methods, classroom dynamics, and students' engagement with grammar-related activities. Interviews with students explore their perceptions in learning grammar, while teacher interviews provide insights into the teaching methodologies employed. The findings of this research contribute to the knowledge on language education, specifically in the context of grammar mastery in tenses. The results can inform educators about the effectiveness of current teaching methods. Additionally, the study may shed light on individual and contextual factors influencing students' grammar proficiency, thus providing valuable insights for future language education strategies. Ultimately, this research aims to enhance the quality of language education at SMK Sinar Husni Medan and contribute to the broader discourse on effective language teaching and learning strategies.